The Synthesis of Oxalate-modified Pyrite/chitosan as an Antibacterial Composite - Rashween Kaur Jagjit Singh; Khee Chung Hui; Nurul Khusna Mohd Salleh; Prakash Peechmani; Farhana Aziz; Hamidah Abdullah; Ahmad Nazrul Rosli; Nonni Soraya Sambudi (Emerald Publishing, 2024)
Indexed by WOS/Scopus